Retrospective Cohort Study Comparing the Epidemiological and Clinical Characteristics between Imported and Local Covid-19 Inpatients in Nanyang, China. (March 2021) - Sun, Chan; Liu, Peipei; Cui, Yanhong; Li, Kefang; Qu, Weiwei; Jin, Bo; Peng, Fei; Zhao, Jiang; Zhang, Xiaoyu
China has experienced an outbreak of COVID-19 since December 2019. This study investigated the differences between the imported and local cases of COVID-19 in Nanyang, China. In this study, a total of 129 COVID-19 confirmed cases with a clear epidemiological history admitted to hospitals in Nanyang from January 24 to February 26, 2020 were enrolled. Patients who had a travel history to or a residence history in Wuhan or in the surrounding areas in Hubei Province within 14 days before the illness onset were assigned to the imported group (n=70), and the others were assigned to the local group (n=59). The differences in epidemiological characteristics, clinical features, laboratory and imaging results, and prognosis were compared between the 2 groups. The early diagnosed cases were mainly imported cases, and the later diagnosed ones were mainly local cases. The most common first symptom was fever; moderate fever was commonly seen in imported cases whereas low fever was commonly seen in local cases. Lymphocyte counts in the imported group were lower than those in the local group. The imported group showed more advanced and severe abnormalities in the CT scan whereas the local group showed milder pulmonary abnormalities. The proportion of severe and critically severe patients in the imported group was higher than that in the local group. In conclusion, the imported cases have more severe or critically severe patients with a higher mortality rate than the local cases.